Efektivitas metode storytelling berbasis nilai-nilai islam terhadap minat baca siswa madrasah ibtidaiyah - ZAMZAM, AKHDAN AYDIN; ZAMZAM, AKHDAN AYDIN (Maliki Interdisciplinary Journal, 2026)
The reading interest of elementary school students remains a challenge in Islamic education in Indonesia. This study aims to analyze the effectiveness of the Islamic values-based storytelling method in increasing the reading interest of elementary school students. The storytelling method was chosen because of its ability to present learning content in an interesting and contextual manner, especially when integrated with Islamic values ​​relevant to students’ lives. This study used a quantitative approach with a quasi-experimental design involving fourth-grade elementary school students as research subjects. Data were collected through reading interest questionnaires, observations, and interviews. The research instruments were tested for validity and reliability before use. The data analysis technique used a t-test to compare the reading interest of the experimental group treated with the Islamic values-based storytelling method with the control group using conventional methods. The results showed a significant difference between the two groups, where the experimental group experienced a higher increase in reading interest. The Islamic values-based storytelling method has proven effective because it is able to create meaningful learning experiences, develop students’ imaginations, and strengthen understanding of Islamic moral values. The implications of this research contribute to the development of literacy learning strategies in Madrasah Ibtidaiyah which not only focus on cognitive aspects but also the formation of students’ Islamic character.